Soundmark: Relasi Soundscape dan Karawitan pada Konsep Pembentuk Ruang - Muhammad Sa'dan Fauzi; Susilo Kusdiwanggo (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
Shadow puppet is the result of the manifestation of Javanese people's knowledge. Karawitan is the sound medium of puppet performance art. Karawitan functions as a shaper of the atmosphere of the shadow puppet show. Space is not only formed by physical factors, but can also be formed by non-physical factors. These non-physical factors usually form not only space, but the meaning and spirit of space are also created at the first time. It-is-important to capture the whole meaning of a space or architectural formations not only with the sense of sight, not just a matter of dimensions. This study aims to answer the question of the relationship formed between soundscape and karawitan pakeliran on the spatial concept. This research is a qualitative research with a meta-analysis strategy. Soundscape is an environmental sound in the form of scenery. Soundmark comes from the landmark, means a sound that is considered unique and is a marker for an area. The sound produced by karawitan can be said as a soundmark. If the karawitan pakeliran can be classified as soundmarks, then the atmosphere formed in the shadow puppet performance can be said to be a manifestation of soundscape.